Interface management for telecommunication system during design stage: a case study of LRT3 project - Peniel, Ang Soon Ern; Nordin, Norimran; Saparudin, Faiz Asraf; Tsai, Kai Len; Kasim, Narimah; Osman, Mohamad Hairi (2024)
Managing the design interfaces of railway projects is challenging and time-consuming due to many complex and inter-dependent interfaces that are embedded within numerous subsystems and work packages. Based on the preliminary study with 2 Interface Managers involved in LRT3 project, it has been found that many interface issues occurred during the design stage due to various reasons. Hence, a case study on the LRT3 project was conducted to propose ways to improve the Interface Management (IM) in LRT3. A semi-structured interview with the IM personnel in LRT3 project was conducted and the IM documentation and tools for the LRT 3 project were reviewed to explore the IM issues and investigate the main factors causing the IM issues during the design stage of LRT3 Project. Subsequently, a practical assessment of the IM framework in the LRT3 Project relating Telecommunication system was conducted where the shortcomings were highlighted and the main IM issues and the factors causing these issues were unfolded. Finally, based on the findings received, a few recommendations were made on how to improve IM in LRT3 project. This research may address the common concerns of project stakeholders with respect to interface management in railway projects and highlights the importance of having an effective IM framework to avoid project delays and conflicts between the interfacing parties